Effect of Sustainability Supply Chain Management on Company Performance: Mediating Role of Competitive Advantage - Hafi, Mohammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to examine effect of sustainability supply chain management on competitive performance with mediating role of competitive advantage. The research was conducted on companies in the manufacturing sector East Java. The data in this study were collected using a questionnaire. Furthermore, 125 questionnaires were distributed in manufacturing company in East Java, but 100 were returned and could be analyzed. Hypothesis testing with Structural Equation Modeling using Smart PLS. The result of the partial analysis show that sustainability supply chain management has a positive and significant effect on competitive advantage, supply chain management has a positive and significant effect on company performance, the last one is competitive advantage has significant effect on company performance. The most important result of this study is competitive advantage has an important role as a mediating variable. Implementation of sustainability supply chain management can increase the company's competitive advantage so that there is an increase in the performance of manufacturing companies in the province of East Java. Competitive advantage can cause companies to have much higher and superior performance than competitors in the industry.